OPTIMISATION OF PRODUCT MARKING ACCURACY THROUGH THE IMPLEMENTATION OF A QR CODE SCANNER SYSTEM BASED ON RASPBERRY PI SBC IN THE AUTOMOTIVE MANUFACTURING INDUSTRY - Ardi, Syahril; Suprapto, Heru; Fadhilah Irfan, Mochamad Nur; Hidayat, M (LPPM Politeknik Astra, 2025)
In automotive manufacturing, accurate product marking is essential for traceability and safety. One interior component requires laser marking of the label